The Pattern of Acetabular Cartilage Wear Is Hip Morphology-dependent and Patient Demographic-dependent - Pascual-Garrido, Cecilia (Clin Orthop Relat Res, 2019)
BACKGROUND: Acetabular cartilage damage has been described in patients with femoroacetabular impingement (FAI). However, most reports of articular cartilage damage in hip FAI have been focused on the acetabular cartilage and derived from single-center, retrospective studies of relatively small patient cohorts. Identifying patterns of articular cartilage wear is important in patient selection, treatment prognosis, and determining whether patterns of intraarticular cartilage wear are secondary to abnormal hip morphology. Using a multicenter, observational cohort, we sought to determine whether there was a specific pattern of cartilage wear across acetabular and femoral articular cartilage among patients with symptomatic FAI. QUESTIONS/PURPOSES: (1) Is there is a specific pattern of cartilage wear in the acetabulum and femoral head, assessed during hip arthroscopy, in cam FAI, pincer, and mixed-type hip pathologies? (2) Are there specific patterns of cartilage wear associated with duration of symptoms, age, and/or body mass index (BMI)? METHODS: A multicenter observational cohort and a hip preservation database from a senior author were used to identify 802 patients who underwent hip arthroscopy for the treatment of symptomatic FAI. The diagnosis of cam, pincer, or mixed-type FAI was determined by each treating surgeon at each institution using the minimum basic criteria of pain in the affected hip for a period of > 3 months, hip ROM, and radiographic findings. Acetabular and femoral head cartilage lesions were classified arthroscopically by location and severity for each group (cam, pincer, or mixed FAI). Cartilage wear was classified using the Beck classification and defined as cartilage lesions greater than Grade 1 (normal macroscopically sound cartilage). The assessment of cartilage wear was performed arthroscopically by experienced hip preservation surgeons who are a part of ANCHOR, a multicenter group that uses a longitudinally maintained database to investigate issues related to hip preservation surgery. Clinical characteristics, radiographic findings, and acetabular and femoral head damage by location and severity of wear were reported based on patient diagnoses of cam (n = 472), mixed (n = 290), and pincer (n = 40) FAI hip pathologies. Wald chi-square tests were used to test for differences in the presence of wear in each cartilage quadrant across hip pathologies, duration of symptoms, age, and BMI. One-way analysis of variance tests were used to test for differences in average grade of wear in each cartilage quadrant across hip pathologies, duration of symptoms, age, and BMI. A bivariate logistic regression model was used to identify factors independently associated with the presence of cartilage wear in the acetabulum and femoral head. Acetabular cartilage wear was present in 743 of 802 patients (93%) in the cohort. Femoral head cartilage wear was observed in only 130 (16%). RESULTS: We found significant associations between acetabular patterns of wear and FAI hip pathologies; specifically, we observed more frequent and severe debonding of acetabular cartilage in patients with symptomatic cam (93%, 1.7 ± 1.1 grade) and mixed (97%, 1.7 ± 1.2 grade) FAI compared with Pincer (75%, 1.5 ± 0.9 grade) FAI hip pathologies (p < 0.001). Superolateral peripheral cartilage lesions occurred more frequently and with greater severity in patients with cam (90% [416 of 472] prevalence, 3.1 ± 1.1 grade) and mixed (91% [260 of 290] prevalence, 3.1 ± 1.1 grade) FAI than in pincer (60% [24 of 40] prevalence, 2.2 ± 1.1 grade) FAI hip pathologies (p < 0.0001). Conversely, patients with pincer FAI most commonly demonstrated cartilage lesions with an even distribution at the anterior and superolateral acetabular rim: 64% (25 of 40) (mean grade 2.1 ± 1.0) and 60% (24 of 40) mean grade 2.2 ± 1.1, respectively. Age was associated with increased presence of wear in both the acetabulum (odds ratio [OR], 1.05; 95% confidence interval [CI], 1.2–1.7; p = 0.005) and femoral head (OR, 1.08; 95% CI, 1.6–1.1; p < 0.001). BMI was associated with a greater presence of wear only in the femoral head (OR, 1.1; 95% CI, 1.2–1.1; p = 0.002). Specifically, compared with patients with a BMI < 30 kg/m(2), patients with a BMI ≥ 30 kg/m(2) presented with more frequent and more severe lesions in the posterior peripheral acetabular rim (42% [47 of 117] versus 26% [171 of 677], p = 0.0006; grade 1.9 ± 1.3 versus grade 1.4 ± 0.9, p < 0.001), the anterolateral femoral head (22% [20 of 117] versus 9% [60 of 67], p = 0.006), and the anteromedial femoral head (15% [16 of 117] versus 6% [39 of 677], p = 0.002; grade 1.3 ± 0.8 versus grade 1.1 ± 0.6, p = 0.04). In general, we found that older patients (≥ 50 years old) presented with more frequent and more severe lesions in both the acetabulum and femoral head. We found no association between hip pathology and cartilage wear patterns in the examined femoral heads. CONCLUSIONS: Hip morphology affects the pattern of acetabular cartilage wear. More frequent and severe cartilage lesions were observed in patients with symptomatic FAI cam and mixed-type hip pathologies. Surgical attempts to restore normal anatomy to avoid FAI should be performed to potentially improve long-term joint homeostasis. Increasing age is an independent risk for cartilage wear in both the acetabulum and femoral head. Additionally, increased BMI is an independent risk factor for cartilage wear in the femoral head. In the future, prospective studies should provide further insight into the pathomechanics of early degenerative changes associated with hip FAI deformities. LEVEL OF EVIDENCE: Level III, prognostic study.